Salicylic Acid Effects on Flue-Cured Tobacco Quality and Curing Characteristics During Harvesting and Curing in Cold-Stressed Fields - He, Xian; Liu, Tianxiang; Ren, Ke; Chen, Jie; Zhao, Gaokun; Hu, Binbin; Xu, Anchuan; Jin, Yan; Zhu, Yanmei; Zou, Congming (Frontiers in Plant Science, 2020)
Salicylic acid (SA) can induce plants to actively enhance abiotic stress resistance. Spraying salicylic acid to prevent cold stress in flue-cured tobacco fields can provide theoretical support and practical guidance for the actual protection from cold stress in fields at high altitude in Yunnan. The experiment was performed in Jianchuan County Yunnan Province, China. Honghuadajinyuan, a flue-cured tobacco variety with cold resistance, was used as the research object. Salicylic acid was tested at two concentrations (0.05 [SA-1]and 0.1 [SA-1] mol L-1) relative to an untreated control (CK) to compare the quality of fresh tobacco leaves, curing characteristics, enzyme activity of antioxidants and quality of the first-cured tobacco leaves. The tissue structure thickness, SPAD and plastid pigment content of fresh tobacco leaves were least in the control; there was no significant difference between SA-1 and SA-2. The change of moisture content during curing was SA-1 > SA-2 > CK, and the water loss rate was CK > SA-2 > SA-1, and both varied greatly at 38-48°C. In each curing stage, the carbon and nitrogen metabolites and polyphenols changed most rapidly at 38°C, and the sugar metabolites changed as follows: CK > SA-1 > SA-2. The activities of the antioxidant enzymes SOD, POD and CAT in fresh tobacco leaves were SA-1 > SA-2 > CK. MDA content, and the inactivation rate of antioxidant enzymes during curing was CK > SA-2 > SA-1. The economic character and sensory smoking quality of flue-cured tobacco leaves were SA-1 > SA-2 > CK. In high altitude tobacco planting areas prone to cold stress in the field, early warning weather forecast and field spraying 0.05 mol L-1 salicylic acid are beneficial to protect and improve the quality of fresh tobacco leaves, curing characteristics, antioxidant system enzyme activities and the quality of flue-cured tobacco leaves.